Efficacy of single-stage breast-conserving treatment using multicatheter partial breast brachytherapy evaluated by GEC-ESTRO phase 3 trial - Sato, Kazuhiko; Fuchikami, Hiromi; Kato, Masahiro; Shimo, Takahiro; Kubota, Jun; Takeda, Naoko; Inoue, Yuko; Seto, Hiroshi; Okawa, Tomohiko (Journal of Contemporary Brachytherapy, 2017)
Purpose : The GEC-ESTRO has reported the equivalent outcomes of partial breast irradiation (PBI) using multicatheter interstitial brachytherapy (MCB) to whole breast irradiation (WBI) in breast-conserving therapy (BCT). We performed single-stage BCT with partial breast brachytherapy by intraoperative catheter placement. After the categorization of patients into inclusion and exclusion criteria on this trial, our databases were evaluated in order to translate it to Japanese patients. Material and methods : Patients undergoing BCT were retrospectively examined between November 2007 and December 2015. The technique is an open-cavity implant with a dose of 32 Gy in 8 fractions. The 4-year clinical outcomes of MCB-PBI were evaluated in the 2 distinct categories, and the comparison of the outcomes of MCB-PBI with WBI was performed in patients with unfavorable features. Results : Of a total of 501 lesions undergoing BCT, 301 lesions were treated with MCB-PBI and 200 lesions with WBI. At the median follow-up time of 52 months, the 4-year rate of ipsilateral breast tumor recurrence (IBTR)-free, disease-free (DFS), and overall survival (OS) in patients with MCB-PBI and WBI were 98.9% vs. 98.0% (p = 0.56), 97.0% vs. 95.3% (p = 0.78), and 99.6% vs. 98.2% (p = 0.38), respectively. Although in exclusion cohort treated with MCB-PBI, IBTR-free, and disease-free survival were significantly worse than in inclusion cohort, non-significantly worse outcomes was demonstrated than in exclusion cohort with WBI; IBTR-free survival (95.0% vs. 97.2%, p = 0.24), and disease-free survival (95.0% vs. 95.8%, p = 0.31). Conclusions : Single-stage BCT using MCB-PBI offered similar tumor control rates compering to WBI. However, further research is needed to define the benefit for patients with an exclusion criteria.